ASSESSMENT OF SEROUS LYMPH HATCHES IN PERITONEAL CARCINOMATOSIS (DIAPHRAGMATIC PERITONEUM) BY SCANNING ELECTRON MICROSCOPY - Sh. Kh. Gantsev; S. V. Solomenny; K. Sh. Gantsev; Sh. R. Kzyrgalin; R. S. Minigazimov; M. V. Loginova (Креативная хирургия и онкология, 2017)
This article describes the results of scanning electron microscopy in cancer. For the first time visualized the cancer cells migrated via directly serous-lymphatic hatches on the surface peritoneum. Shown the similar results of studies of Japanese scientists, but selected the differences in the mechanisms of this process, in particular in the direction of movement of cancer cells. From data analysis results of quantitative and anatomical evaluation of serous lymph hatches diaphragmatic peritoneum we selected their functional classes. Investigation results have important applied value in oncology.